Perbedaan Frekuensi Konsumsi Fast Food Dan Aktivitas Fisik Pada Remaja Overweight Dan Tidak Overweight Di SMA Nasima Semarang - Hidayati, Annisaa nuur, Wahyuni, S.Ft., M.Kes, Ruli Sudaryanto, SST (2016)
Introduction: Fast food industry has been affecting eating patterns. Nowadays, teenagers tend to have less activity followed by badeating habit lead to energy saved as fast. Therefore, the number of obesity has been increasing because of the unbalance between the intakes of energy with the number of energy requirement. Objective: The aims of this study was to determine differences between fast food frequency consumption and physical activity between the fequency overweight and not overweight students in Nasima Senior High School of Semarang. Methods: This study was an observational study with case control study design. Frequency of fast food consumption data obtained by a food frequency questionnaire first semi last month, physical activity data obtained by physical activity recall for 3 days and nutritional status data overweight using BMI indicator/U. Subjects numbered 84 people were taken by purposive random sampling. The statistical test used to analyze the relationship was the Kolmogorov-Smirnov normality test and Man Whitney. Results: Overweight adolescent have fast food frequency consumption seldom and often each amounting to 50% (21 persons). Not overweight adolescent more have fast food frequency consumption often 76,2% (32 persons), was tested by the statistic have p value =0,843. Overweight adolescent more have done light physical activity 95,2% (40 persons) and not overweight adolescent more have done light physical activity equal to 85,7%(36 persons), was tested by the statistic have p value =0,02. Conclusion: There was differences fast food frequency consumption between overweight and not overweight students (p=0,843). There was not differences the physical activity between overweight and not overweight students (p=0,002). Suggestion: It was better for school held colaboration with health center to provide information about effect of fast food and the important of physical activity for health. Beside that it was better for further research so that add to span the time of intake the physical activity data